The Effect of Edamame Concentration as Emulsifiers on the Physicochemical Properties of Egg-Free Cookies - Ramanda, Muhammad Rizky; Jaelani, Arthinita; Fitria, Agnes Nabila; Talitha, Zada Agna (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Cookies are defined as small-sized, low moisture bakery products known for their crispy texture and sweet flavor. The process of making cookies requires an emulsifier to produce a more compact and sturdy dough and act as a stabilizer. The emulsifier used in cookie making is egg. Standard cookie recipes often use 1 whole egg per 100–150 g of flour. However, the high cholesterol content in eggs can cause increased blood cholesterol levels, atherosclerosis, and increase the risk of coronary heart disease, high blood pressure, and stroke, thus necessitating the replacement of egg yolk in cookie making. Whole chicken egg (±50 g): 186–200 mg cholesterol. Generally, there are many types of synthetic and natural emulsifiers used in the food industry, including proteins, phospholipids, polysaccharides, and surfactants. One protein used because of its emulsifying ability is plant protein from soy. Soy products with potential to replace egg yolk are Edamame. The research was conducted with two repetitions and analyzed in duplicate using One Way ANOVA at a 5% significance level. The results of using edamame as an emulsifier in cookies showed hardness texture (7.50N-17.41N), cohesiveness texture (0.38-0.98), springiness texture (2.01mm-3.20mm), color L (43.59-43.66), color a (2.69-2.71), color b* (4.16-7.79), color deltaE (0.41-3.64), moisture content 4.29%-6.51%, ash content 1.92%-2.67%, protein content 3.54%-5.04%, fat content 23.31%-24.85%, and carbohydrate content 60.93%-66.64%. This research shows that adding edamame at the highest concentration results in a softer texture and higher moisture content, fat, and protein content. Therefore, based on this research data, edamame can be used as an egg substitute in cookies. Keywords: cookies, edamame, emulsifier, plant-based protein, egg-free product